OPTIMIZATION OF IMPORTED SOYBEAN SUPPLIER SELECTION USING AHP AND SWOT METHODS - eki (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2023)
OPTIMIZATION OF IMPORTED SOYBEAN SUPPLIER SELECTION USING AHP AND SWOT METHODS